The walking dead. Vol. 08, Made to suffer - Kirkman, Robert (Kirkman, Robert. Walking dead., 2008)
A group of survivors on the outside launch an attack on zombies in a prison where Rick and his group believed they were safe, and the full-scale battle that ensues results in a high body count.